Analisis Gaya Belajar Berdasarkan Asal Sekolah pada Perkuliahan Fisika Terapan - Lusiani Lusiani; Andi Hendrawan; Fajar Firmansyah; Supriyanto Supriyanto (KOLONI, 2024)
All in the education sector, including educators, students, parents and the school environment, need to know that the learning style used by each student is an important thing that is important to pay attention to. The problem with lectures is that most educators do not know that there are differences in individual learning styles and do not manage them well. The aim of the following study is to analyze learning styles based on school origin in applied physics courses. This study uses a research method combining observation and literature review. The author took place at the AMN Cilacap Engineering Study Program by utilizing an instrument in the form of media, namely Google Form. It was concluded that the analysis of learning styles based on school origin in applied physics lectures between High School (SMA) and Vocational High School (SMK) students was comparable or relevant, namely option 2 which was an auditory learning style.